Proceedings of the 2018 Conference of the ACM Special Interest Group on Data Communication 2018
DOI: 10.1145/3230543.3230580
|View full text |Cite
|
Sign up to set email alerts
|

Networking across boundaries

Abstract: The MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Optical communication underwater presents a lot of promise to solve this persistent challenge, however, these technologies are in their infancy. [25][26][27][28] Thus, an alternative approach is to store the data in the memory embedded on the platform and transfer the stored data when the animal comes to the surface of the water during its natural behavior. Hueter et al recently demonstrated the usage of a satellite-linked MiniPAT TM system for tracking the movement of Carcharhinus falciformis (silky shark) to understand the ecology of this large, oceanic species.…”
Section: Resultsmentioning
confidence: 99%
“…Optical communication underwater presents a lot of promise to solve this persistent challenge, however, these technologies are in their infancy. [25][26][27][28] Thus, an alternative approach is to store the data in the memory embedded on the platform and transfer the stored data when the animal comes to the surface of the water during its natural behavior. Hueter et al recently demonstrated the usage of a satellite-linked MiniPAT TM system for tracking the movement of Carcharhinus falciformis (silky shark) to understand the ecology of this large, oceanic species.…”
Section: Resultsmentioning
confidence: 99%
“…No single networking standard is self-sufficient for all these communication boundaries; hence, cross-technology communication is needed. Tonolini et al [92] investigated interboundary communication between air and water. A robust wireless network that can withstand the effect of changes in environmental factors (temperature, relative humidity, multipath, etc.)…”
Section: F: Warehouse Receipt System (Wrs)mentioning
confidence: 99%
“…Stationary relays, lack of mobility TARF [10] (Acoustic-RF) 400 bps 1 m Relay-free, strict alignment A-O [11] (Acoustic-optical) N.A. N.A.…”
Section: Modalitymentioning
confidence: 99%
“…Alternatively, by combining two techniques without using gateways, such as in acoustic RF [10] or acoustic-optical light [11], communications across water-air interface have also been demonstrated. By sending acoustic waves underwater (which travel as pressure waves), inducing the displacement of the water surface, and using RF or optical beams to detect the displacement, the MIT Media Lab [10] and U.S. Navy [11] demonstrated such across-water-air interface communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation